Professional Features of IT Specialists’ Activities as Burnout Risk Factors - Alena F. Dzhumagulova; Natalia E. Vodopyanova; Olga O. Gofman; German S. Nikiforov (RUDN Journal of Psychology and Pedagogics)
Currently, there is a high demand for IT specialists in the Russian economy. To build a long-term strategy for their selection and psychological support in a company, it is necessary to identify and understand the risks of developing stress syndromes (including burnout) in them, depending on the conditions of their professional activity, and make a comprehensive description of their professional profile. The article describes the features of the digitalization of society and their impact on the professional burnout of an IT specialist. The purpose of this study is to identify the profession-specific features of the activities of IT specialists in terms of the risks of burnout development. The study used (1) a semi-structured expert interview on the representation of IT-specialists about the features, requirements and conditions of their work (containing five groups of questions on technological and economic features, educational and medical requirements, and psychological aspects of professions in the IT field); and (2) a questionnaire survey in a Google form about the features of time management in different areas of life. The interview and the questionnaire covered 19 and 82 IT experts, respectively. Based on the analysis of the obtained data, the authors were able to determine: (1) the job duties of representatives of the professions of ‘programmer’, ‘analyst’ and ‘tester’; (2) the most common causes of professional errors in the IT sphere, as well as their consequences as risk factors for burnout; (3) the minimum level of training, educational requirements and criteria for success in activities; (4) the most common cognitive and social work operations of IT professions; (5) requirements for the level of health and working conditions, as well as possible occupational diseases; and (6) data on the imbalance of work and rest, work and personal life. The study revealed possible risk factors for emotional exhaustion, depersonalization, and reduction in personal achievements of IT specialists. Finally, conclusions are made that the digital environment significantly influences the information environment around an IT specialist, transforms the perception of time, space, information, methods of communication and self-presentation, and changes the motivational sensory-cognitive involvement in work.